Analisis Pengaruh Ekuitas Merek, Preferensi Merek, dan Harga Dengan Citra Negara Asal sebagai Variabel Moderasi Terhadap Minat Pembelian Laptop Oleh Mahasiswa di Kota Batam - Lily Purwianti; Mehdar Badrus Zaman (Jurnal Manajemen dan Bisnis Indonesia, 2017)
The main purpose of this study is to investigate the relationships among brand equity, brand preference, price and purchase intention. Moreover secondary aim of this research is examining the moderate role of country of origin image. Independent variables used in this research are brand equity, brand preference and price. Data were collected from 500 students in Batam who recognized the selected brand of laptop using judgmental sampling from 5 universities they are Universitas Putera Batam, Universitas Riau Kepulauan, Politeknik Negeri Batam, Universitas Internasional Batam, and Universitas Batam. Hypotheses were tested using SPSS program version 21. Results indicated that brand equity, brand preference and price positively influence consumer’s purchase intention. But results unsupported moderating role of country of origin image in the relationships among brand equity, brand preference and purchase intention. Keywords: brand equity, brand preference, price, country of origin and purchase intention.